Sliding frictional contact between a square block and an elastically similar half-plane - Karuppanan , S; Churchman, C; Hills, D; Giner, E (2008)
The contact pressure distribution beneath a square block sliding along an elastically similar half-plane, in the presence of friction,is found. The considerable effect of the coefficient of friction on the trailing edge pressure distribution, and, in particular, the transition from power order behaviour to local separation and bounded behaviour when the coefficient of friction exceeds 0.392 is examined, and an appropriate asymptotic form developed.